Variation of rectal temperature in dogs undergoing 3T-MRI in general anesthesia - Paul, Frauke; Alef, Michaele (Frontiers in Veterinary Science, 2023)
Objectives: Managing body temperature during MRI scanning under general anesthesia poses challenges for both human and veterinary patients, as many temperature monitoring devices and patient warming systems are unsuitable for the use inside an MRI scanner. MRI has the potential to cause tissue and body warming, but this effect may be counteracted by the hypothermia induced by general anesthesia and the low ambient temperature usually encountered in scanner rooms. This study aimed to observe temperature variations in dogs undergoing MRI under general anesthesia. Material and methods: In this prospective observational study, client-owned dogs scheduled for 3-Tesla MRI under anesthesia between February and October 2020 at a veterinary teaching hospital were eligible for enrollment. Recorded data included breed, body mass, body condition score, age, fur quality, pre- and post-MRI rectal temperatures, time in the MRI room, scan area and coil used, application of contrast medium, choice of anesthetic agents, use of blankets, and infusion therapy. Group comparisons were conducted using the Mann-Whitney U-test or Kruskal-Wallis test, with p < 0.05 considered significant. Results: In total 171 dogs met the inclusion criteria. The median body temperature at admission was 38.4°C (IQR 38.1 -38.7°C). The median body temperature before MRI was 38,2°C (IQR 37.8 – 38.6°C), and the median temperature after the MRI scan was 37.7°C (IQR 37.2 – 38.2°C) resulting in a median temperature difference (∆T) before and after MRI of - 0.6°C (IQR -0.8 - -0.1°C). The median duration of MRI scans was 49 minutes (IQR 38 -63 min). A temperature loss of more than 0.1°C was observed in 121 (70.8%) dogs, 29 (16.9%) dogs maintained their temperature within 0.1°C, and 21 (12.3%) dogs experienced a temperature increase of more than 0.1°C. Factors associated with a higher post-MRI temperature included greater body mass, medium or long fur, and the application of α2- receptor-agonists. Conclusion: Dogs undergoing MRI under general anesthesia are likely to experience temperature loss in the given circumstances. However, in larger dogs and those with much fur, an increase in body temperature is possible and more common than generally anticipated, although clinically insignificant in most cases.